China's Pure Exporter Subsidies - Fabrice Defever; Alejandro Ria\~no (FIW - Research Centre International Economics, 2013)
One third of Chinese exporters sell more than ninety percent of their production abroad. We argue that this distinctive pattern is attributable to the widespread use of subsidies that require firms to export the vast majority of their output. We study this type of subsidy in the context of a heterogeneous-firm model, and show that it is worse from a welfare standpoint than a regular export subsidy, partly because it increases protection of the domestic market. A counterfactual analysis suggests that eliminating these subsidies would result in a welfare gain for China comparable to that of halving its trade costs.
Keywords: F12; F13; O47; 330; Trade Policy; Export Subsidies; Heterogeneous Firms; China